Personality Tests in Employment: A Continuing Legal, Ethical, and Practical Quandary - Mujtaba, Bahaudin G. (Advances in Social Sciences Research Journal, 2015)
The controversy in human resource practice and law today continues, to wit: –the use of personality tests in employment, typically online tests, which human resource practitioners are increasingly using in the hiring process, especially for executives, sales, and customer service positions. Selecting the right people for the right positions is, of course, one of the elements of success for any business. Accordingly, it is imperative for the employer to choose highly qualified people for open positions. This article examines the effectiveness, legality, fairness, and morality of personality tests in employment. Legal aspects of the use of personality tests are examined, principally pursuant to the U.S. Civil Rights Act and the Americans with Disabilities Act. An ethical analysis of personality tests is provided to determine if their use in the context of employment is moral. The legal focus of the article is primarily on the private sector, but the principles are applicable across the board. The implications of the use of personality tests in employment are raised; and accordingly several recommendations are supplied to achieve a legal, moral, and practical use of personality tests in employment.